2020
DOI: 10.1101/2020.11.23.20237149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental efficacy of the face shield and the mask against emitted and potentially received particles

Abstract: The aim of this study was to evaluate the comparative performance of masks and face shields in different experimental configurations. An experimental setup with two mannequin heads positioned at 1.70m high and at 25 cm each other was used. A fogger generated a particle’s airflow with a speed of 5m/sec from the emitter to the receiver head mannequin. Our aerosol generator produced 3 000 times more particles than a physiological cough situation. A particle counter allowed us to evaluate the number of particles r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…0.14 µm for SARS-CoV-2) [ 13 , 25 , 26 , 27 ]. Face masks serve to reduce the number of particles, especially heavier ones [ 17 , 28 , 29 ]. Considering this, more attention should be paid to small particle sizes (diameter < 1 µm) when indoor viral aerosol dispersion is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…0.14 µm for SARS-CoV-2) [ 13 , 25 , 26 , 27 ]. Face masks serve to reduce the number of particles, especially heavier ones [ 17 , 28 , 29 ]. Considering this, more attention should be paid to small particle sizes (diameter < 1 µm) when indoor viral aerosol dispersion is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory studies using mannikins have examined the potential effects of face shields but vary greatly in their design and their application to real-world settings. One study tested facing mannikins 25cm apart with the emitter sending an aerosol spray with particles with a range of size from less than 0.3µm to 10 µm; they found a reduction in particles received of 55% with face shields compared to 22% for a mask, and 97% for both 18 . A study with a mannikin 60cm from the spray found greater reductions and face shields providing greater protection than masks 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratory studies using mannikins have examined the potential effects of face shields but vary greatly in their design and their application to real-world settings. One study tested facing mannikins 25cm apart with the emitter sending an aerosol spray with particles with a range of size from less than 0.3µm to 10 µm; they found a reduction in particles received of 55% with face shields compared to 22% for a mask, and 97% for both 18 .…”
Section: Discussionmentioning
confidence: 99%